Pengaruh Kualitas Audit, Pertumbuhan Perusahaan, Dan Opinion Shopping Terhadap Penerimaan Opini Audit Going Concern - Rani Rani; Nayang Helmayunita (Jurnal Eksplorasi Akuntansi, 2020)
This study aims to examine the effect of changes in audit quality, company growth, and opinion shopping on going concern audit opinion acceptance. This type of research is a causative research. The population used in this research is all mining sector companies and the transportation sub-sector listed on the Indonesia Stock Exchange in 2014-2018. The sampling technique in this study using purposive sampling technique, there are 60 mining companies and 35 transportation companies that are used as research samples. The data used in this research is secondary data obtained from the official website of the Indonesia Stock Exchange or the official website of each company. The analysis method used is the panel data regression method because it consists of several data and years. The results showed that company growth had a significant negative effect on going concern audit opinion acceptance, but audit quality and opinion shopping could not have a significant effect on going concern audit opinion acceptance.